Errors in Complete Denture Fabrication during Pre-clinical Learning by Dental Students in Chitwan - Mishra Sapkota, Srijana; Pandey, Anisha; Thakur, Smriti Narayan; Khanal, Bibek (Journal of Karnali Academy of Health Sciences, 2021)
Introduction: Preclinical dental skills are necessary for the dental students and it is also a prerequisite for the success of a competency based dental curriculum. This will enhance the future clinical practice. Dental students also experience difficulties during the transition from preclinical posting to clinical practice. Hence, this study was aimed to assess the errors in preclinical complete denture fabrication by the dental students in Chitwan. Materials and methods: A descriptive cross-sectional study was conducted among the dental students of Chitwan from January 2021 to April 2021. Seventy Ideal Complete Dentures fabricated by undergraduate dental students were evaluated on basis of parameters like porosity in master cast, adaptation and porosity in record bases, occlusion rim, mounting, axial inclination of anterior and posterior teeth, horizontal & vertical glass plate relationship, occlusion, carving. The data collected were analyzed for frequency and percentage of occurrence. Results: The most common error made by preclinical students was lateral glass plate relationship (51.4% in our study) followed by fabrication of occlusion rim (48.5%). The least common error was in porosity of master cast about 10%. Conclusion: There is high possibility of incorporating error during complete denture fabrication by undergraduate dental students. The study focuses the need to explore the modification of teaching learning methods of prosthodontics with the use of simulators and visual aids